X=(20-2x)*(40-2x)

Simple and best practice solution for X=(20-2x)*(40-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X=(20-2x)*(40-2x) equation:


Simplifying
X = (20 + -2x)(40 + -2x)

Multiply (20 + -2x) * (40 + -2x)
X = (20(40 + -2x) + -2x * (40 + -2x))
X = ((40 * 20 + -2x * 20) + -2x * (40 + -2x))
X = ((800 + -40x) + -2x * (40 + -2x))
X = (800 + -40x + (40 * -2x + -2x * -2x))
X = (800 + -40x + (-80x + 4x2))

Combine like terms: -40x + -80x = -120x
X = (800 + -120x + 4x2)

Solving
X = 800 + -120x + 4x2

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Simplifying
X = 800 + -120x + 4x2

See similar equations:

| 14n+2=72 | | 10(s-5)=-98 | | x=(20-2x)(40-2x) | | f(x)=2senx | | x^4+x^3-8x^2+16x+6=0 | | 225=x^2-16x+68 | | 0=y^2-4y-1 | | 3(3s+6)=72 | | 29+5y-2=15y-13-2y | | x+2x+1+8x-1+3x+2=58 | | 5(t-6)=5 | | F(x)=x-2.5 | | 0.9x=0.9 | | 12x^2-3x=o | | 10x+6-32=-88 | | 4(a-7)=68 | | 5a+34=-2(1-7a) | | 2n-10=50 | | f(x)=4x^3+3x^2+2x^1+0x^0 | | 3y+1+6-13=180 | | r+-5r=4r | | 8-(h+1)=9-(2h-1) | | y^2-4y-67=0 | | 6a=3.60 | | 2x+4x-2=15 | | 2x+3-5x+2=7x+4-6x | | 5/9=×/18 | | Log3/log4 | | X9=15/2 | | 3q*q= | | 8x+17= | | 7=46 |

Equations solver categories